Green Synthesis of Porous Spherical Reduced Graphene Oxide and Its Application in Immobilized Pectinase - Gao, Min (ACS Omega, 2020)
[Image: see text] Pectinase is widely used in juice production, food processes, and other fields. However, owing to poor stability, free pectinase is difficult to separate from a substrate after hydrolysis and cannot be reused, and thus its industrial use is limited. Immobilized pectinase can solve these problems well. We prepared a carrier material of immobilized enzyme, which is called porous spherical reduced graphene oxide (rGO) with a rich pore structure, large specific surface area, strong hardness, and good biocompatibility to enzyme. Then, we evaluated the performance of the porous spherical rGO immobilized pectinase and characterized its structure by IR, XRD, and SEM. Using this material as a carrier of immobilized enzyme improves the load and catalytic activity of the enzyme. After 10 times of continuous use, the porous spherical rGO immobilized enzyme still maintained its initial relative enzyme activity at around 87%, indicating that immobilized pectinase had a stronger cycling stability, and its thermal stability, acid–base tolerance, and storage stability were superior to those of free pectinase. The results were compared with those of other studies on immobilized pectinase. The relative activity of pectinase immobilized by porous spherical rGO was at a high level after 10 consecutive uses. Overall, the spherical rGO is an excellent immobilized enzyme carrier material.